Chiral Separation of Aspartic Acid by Thin-Layer Chromatography - K. KATIYAR, PRASHANT; KABRA WALA, RAVI (Asian Journal of Chemistry, 2010)
In this study, chiral separation of D/L-aspartic acid was achieved by thin layer chromatography using L-arginine as a chiral separator using the mobile phase as butanol:glacial acetic acid:water (70:10:20) and the visualizing agent is ninhydrin and butanol (20:10).